Principal Leadership Model Based on Prophetic Values in Improving the Quality of Education at Mts Abu Bakar Al-Islamy Sumbawa - Ibrahim Obet; Akhmad Shunhaji (Edukasiana: Journal of Islamic Education, 2025)
Abstract Model of Principal Leadership Based on Prophetic Values in Improving the Quality of Education at Mts Abu Bakar Al-Islamy Sumbawa. This research aims to determine the redefinition of the prophetic-based leadership model in educational institutions, the application of prophetic-based leadership at MTs Abu Bakar Al-Islamy Sumbawa and the prophetic-based leadership model at MTs Abu Bakar Al Islmy Sumbawa in improving the quality of education. The method used in this research or study is qualitative and the approach used is descriptive naturalistic. The results of this research are: 1) The meaning of the prophetic leadership model in educational institutions cannot be separated from the main elements contained in the structure of prophetic values constructed in the Al-Qur'an Al-Imran verse 110, namely humanization, liberation and transcendence. Humanization as a derivation of amar ma'ruf implies humanity. Liberation taken from the verses of nahi mungkar implies liberation/freeing. And tu'minu billah which means transcendence is a factual dimension of human faith as a creature created by Allah SWT. 2) Implementation and internalization of values and or norms so that they become awareness which is manifested in attitudes and daily behavior. Thus, the internalization of the values of prophetic leadership in Islamic educational institutions is intended to consciously manifest these leadership values in the attitudes and behavior of institutional leaders, which in turn can also be internalized within the entire academic community of Islamic educational institutions. 3) prophetic leadership must depart from the starting point of a theological paradigm, namely from God, because of God and "for God". From God means that the leadership currently carried comes from God. The motive for leadership comes from God, and it is by God's grace that humans can become leaders.